Data Dive- mobile for nutrition. - Hachhethu, Kusum.; Farhikhtah, Arghanoon.; Lamanna, Christine.; Ngendo, Mary. (Tufts University. Tisch Library., 2017)
In this highly interactive session, we 'dive' into the data that we collected by mobile technology in Kenya and Malawi. We show how data collected from face to face interviews differs from data collected through mobile tools. Participants were able to take surveys on their own phones (or sample phones provided for) in an interactive demo.